Analysis of the main differences in the implementation of alternative strategies between hedge funds and UCITS (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
In recent years, the UCITS industry’s applicable legislation has evolved tomake UCITS more similar to hedge funds. However, and regardless the fact that UCITS currently have a great number of investment possibilities, they still have difficulties when implementing certain strategies as a result of the restrictions and limitations imposed by applicable law, which is primarily aimed at protecting investors. Therefore, this study analyzes the main problems of UCITS when implementing strategies similar to those implemented by hedge funds, as well as the advantages and disadvantages of UCITS funds derived from the limitations and restrictions faced by these investment vehicles.
Keywords: UCITS funds; hedge funds; strategies; differences; restrictions; limits; legislation; advantages; disadvantages.